2019
DOI: 10.1016/j.ijid.2019.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Chagas disease in the Bolivian Chaco: Persistent transmission indicated by childhood seroscreening study

Abstract: Background: Screening for Trypanosoma cruzi infection was performed amongst children in a rural community in the Bolivian Chaco, an area known for high prevalence. The force of infection (FOI) was estimated. Methods: A total of 423 children attending the local school were screened using the Chagas Detect Plus (CDP) rapid test (InBios International, Inc.). CDP-positive specimens were further tested by indirect haemagglutination assay (IHA) and Wiener Recombinante v3.0 ELISA. A catalytic model was used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…During the current study, the prevalence of T. cruzi infection in children (2-15 year old) in Itanambikua was 20% [18]. Similar childhood infection seroprevalences are reported for nearby Guarani communities, showing an increase in prevalence with age with the vast majority of residents >30 years old infected [17].…”
Section: Study Sitesupporting
confidence: 81%
See 4 more Smart Citations
“…During the current study, the prevalence of T. cruzi infection in children (2-15 year old) in Itanambikua was 20% [18]. Similar childhood infection seroprevalences are reported for nearby Guarani communities, showing an increase in prevalence with age with the vast majority of residents >30 years old infected [17].…”
Section: Study Sitesupporting
confidence: 81%
“…In contrast, IRS activities against Tri. infestans vectors in the Gran Chaco region have not been noticeably successful evidenced by the high incidence of vector-borne transmission [16, 17, 18, 28, 29]. This study evaluated IRS practises and procedures in Itanambikua, identified as one such focus of chronic vector-borne transmission [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations